Opedipal God: The Chinese Nezha and his I ndian Origins, by Meir Shahar. (2nd October 2019) - Collins, Brian
Abstract : Opedipal God: The Chinese Nezha and his I ndian Origins, by Meir Shahar. Honolulu: University of Hawai'i Press, 2015. 312 pp., £49.95 (hb). ISBN 9-780-824-847609.